2019
DOI: 10.1017/s0007114519000709
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lifelong carnitine supplementation on plasma and tissue carnitine status, hepatic lipid metabolism and stress signalling pathways and skeletal muscle transcriptome in mice at advanced age

Abstract: While strong evidence from clinical studies suggests beneficial effects of carnitine supplementation on metabolic health, serious safety concerns associated with carnitine supplementation have been raised from studies in mice. Considering that the carnitine doses in these mice studies were up to 100 times higher than those used in clinical studies, the present study aimed to address possible safety concerns associated with long-term supplementation of a carnitine dose used in clinical trials. Two groups of NMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Supplemented mice had significantly higher free carnitine concentrations at time of sacrifice than non-supplemented mice (44.3±5.0 vs. 39.7±4.9 μM, p=0.04). Though a modest difference, other studies supplementing mice with similar doses of LC report variability in the effect on serum/ plasma carnitine levels, ranging between approximately 0.65 to 20 μM higher [32][33][34][35].…”
Section: Carnitine Levelsmentioning
confidence: 89%
“…Supplemented mice had significantly higher free carnitine concentrations at time of sacrifice than non-supplemented mice (44.3±5.0 vs. 39.7±4.9 μM, p=0.04). Though a modest difference, other studies supplementing mice with similar doses of LC report variability in the effect on serum/ plasma carnitine levels, ranging between approximately 0.65 to 20 μM higher [32][33][34][35].…”
Section: Carnitine Levelsmentioning
confidence: 89%
“…Both LC and NR effects on plasma metabolic risk factors may be dose dependent. LC with 2000 mg daily for 24 weeks resulted in lower glucose and plasma lipid levels in NASH patients [31] as well as improved insulin sensitivity [32], whereas 19 months treatment with a very low dose of 100 mg/kg LC daily in mice did not reveal any significant effects on plasma lipid levels [33]. Similarly, studies in mice reported lowering effects of 400 mg/kg NR on ALT [27], fasting glucose and an improvement in insulin sensitivity [9,29].…”
Section: Discussionmentioning
confidence: 99%
“…The phthalates were first dissolved in absolute ethanol, then incorporated into food as previously detailed (Ahmadpour et al, 2021 studies showing an external co-exposure to these molecules and the presence of their metabolites in urinary samples (Dewalque et al, 2014;Martine et al, 2013). Mice were weighed weekly for the duration of the exposure and phthalate doses were adjusted to their body weights and calculated for a daily food intake of 5 g per animal (Cheema et al, 2019;Dombret et al, 2017). It has already been shown that such a phthalate exposure protocol had no effect on the body weight of individuals between the first and the last day of treatment (Ahmadpour et al, 2021).…”
Section: Phthalate Exposurementioning
confidence: 99%